Diabetes Is Not Associated with Increased 10-week Mortality Risk in Patients with Cryptococcal Meningitis - Lijun Xu; Ying Chen; Minghan Zhou; Ran Tao; Yongzheng Guo; Fangyuan Lou; Zongxing Yang; Haijuan Wang (​​​​​​​​Infectious Diseases & Immunity, 2022)
Abstract. Background:. Diabetes is a risk factor for acquisition of cryptococcal meningitis (CM). However, the effects of diabetes on outcomes of CM patient have not been fully studied. Methods:. In this retrospective study, 49 diabetic CM patients and 98 non-diabetic CM patients from January 2008 to December 2018 in the First Affiliated Hospital of Zhejiang University were included by propensity score-matched method (1:2). Demographic characteristics, symptoms, and clinical assay parameters between the two groups were compared. Kaplan-Meier analysis and Cox proportional hazards model were used to assess factors associated with 10-week mortality. Results:. The mean age of diabetic patients was 58.2 ± 13.8 years; 71.4% (35/49) were more than 50 years old and 46.9% were male. No difference in symptoms was found between diabetic and non-diabetic CM patients. The Charlson comorbidity score was higher in the diabetic group (1.9 vs. 0.7, P < 0.001). CM patients with diabetes had higher white blood cells count (×106 /L, 111.0 (18.0– 242.5) vs. 50.0 (10.0–140.0), P = 0.034) in cerebrospinal fluid (CSF), lower CSF India ink positivity (40.8% vs. 60.2%, P = 0.039), and Cryptococcus culture positivity (42.9% vs. 60.2%, P = 0.047). The overall 10-week survival rate was 79.7% in diabetic patients vs. 83.2% in non-diabetic patients (log-rank P = 0.794). Conclusion:. Diabetic CM patients have higher CSF glucose and Charlson comorbidity score, but lower CSF India ink and culture positivity than non-diabetic CM patients. No difference in 10-week mortality was found between patients with and without diabetes. Other comorbidities may have a greater effect on prognosis.